Distribution, health and threats to Mediterranean macroalgal forests: defining the baselines for their conservation and restoration - Verdura, Jana; Rehues, Lluc; Mangialajo, Luisa; Fraschetti, Simonetta; Belattmania, Zahira; Bianchelli, Silvia; Blanfuné, Aurélie; Sabour, Brahim; Chiarore, Antonia; Danovaro, Roberto; Fabbrizzi, Erika; Giakoumi, Sylvaine; et al. (Frontiers in Marine Science, 2023)
The worldwide decline of macroalgal forests is raising major concerns for the potentially negative consequences on biodiversity and ecosystem functions, pushing for the definition of specific conservation and restoration measures. Protecting and restoring these habitats requires detailed information on their distribution, ecological status, and drivers of decline. Here, we provide the most updated available information on the distribution of Mediterranean Cystoseira s.l. forests by conducting a comprehensive bibliographic survey of literature published from 2009 to 2021, complemented by unpublished data. We also provide insights into the ecological status of these forests and the stressors affecting them across the Mediterranean basin. Our results show that most Mediterranean coasts remain un(der)studied and that the available information is concentrated in spatially limited coastal areas, restricted to very few species. When the ecological status is reported, data is highly heterogeneous, making any comparisons problematic, what claims for the description and use of easy and standardized monitoring methods for comparative purposes. Drivers of decline of Cystoseira s.l. forest have been even less investigated and, therefore, still poorly characterized. Our results highlight that our current knowledge is still insufficient to implement effective conservation and restoration strategies at the basin scale but also regionally. We call for the urgent need for mapping and standardized monitoring of Cystoseira s.l. forests to obtain baseline information for future management strategies involving their conservation, the mitigation of the stressors threatening them and the restoration of the degraded forests.